A Look at Human Trafficking and the Anti-Trafficking Apparatus in Mexico through the Experience of Victoria, a Trans Woman - Maldonado Macedo, Juliana Vanessa; Jiménez Portilla, Luz del Carmen (Anti-Trafficking Review, 2024)
In this article, we discuss the experience of Victoria, a trans woman who was trafficked in the context of the criminal war in Mexico. Drawing on anthropological and feminist perspectives that privilege the dialogue of knowledge, Victoria’s experience allows us to problematise two central elements of the phenomenon of human trafficking in Mexico: first, the relationship between organised crime groups and human trafficking, and its effects on daily life in local contexts in Mexico, specifically in the experience of a trans woman. And second, the functioning of the Mexican anti-trafficking apparatus which, by focusing on the rescue of victims of sexual exploitation in places where independent sex work occurs, overlooks the identification of other forms of trafficking, such as trafficking for labour exploitation and servitude, both experienced by Victoria at the hands of organised crime groups.